Making children's 'agency' visible: Towards the localisation of a concept in theory and practice. Issue 3 (September 2019) - Edmonds, Ruth
The concept of 'agency' is regularly put forward as an analytic tool to help understand, evaluate and act upon places around the world, through social development policies and programmes ostensibly designed to support or increase children's agency. This article reflects on empirical research into children's agency spanning a range of international contexts over two decades and offers new insights through critical engagement with a growing body of work on the 'localisation' of social development and humanitarian responses in international settings. It suggests that the largely normative ways in which the concept of agency is invoked as an analytic tool for understanding human experience universally effectively renders children's agency invisible to us. This is because it is more a description of a particular discourse than something which actually helps us to understand and make visible children's socio-culturally grounded 'agentic practice' from place to place. This article argues for new directions in research and practice to localise agency that are critical to the central commitments of interpretive social science. These new directions include (a) a new research agenda which can go beyond children's 'own perspectives' to the discovery, description and analysis of agency in socio-cultural terms, to ensure it can function as an analytic tool for learning about socio-cultural phenomena which help animate local concepts of agency; and (b) the development of agency-related policies and programmes that are grounded in such locally situated concepts of agency developed through understanding local socio-cultural systems rather than externally derived socio-cultural assumptions about childhood and children's agency.